Concurrent production of interleukin-2, interleukin-10, and gamma interferon in the regional lymph nodes of mice with influenza pneumonia. - Sarawar, S R (1994)
Cytokine production has been assessed at the single-cell level (ELISPOT assay) for freshly isolated mediastinal lymph node cells from C57BL/6 mice with primary, nonfatal influenza pneumonia. The mediastinal lymph node populations were also secondarily stimulated in vitro, and culture supernatants were assayed by enzyme-linked immunosorbent assay. Both approaches showed minimal evidence of protein secretion for interleukin-4 (IL-4), IL-5, and tumor necrosis factor, while IL-2, IL-10, and gamma interferon (IFN-gamma) were prominent throughout the response. The numbers of IL-2- and IFN-gamma-producing cells were maximal at 7 days after infection, while the total counts for cells secreting IL-10 were fairly constant from day 3 to 7. The cultures that were stimulated with virus in vitro showed in inverse relationship between IL-10 and IFN-gamma production, with IL-10 peaking on day 3 and IFN-gamma peaking on day 7. Lymphocytes secreting IL-2, IL-10, and/or IFN-gamma were present in CD4+ and CD8+ populations separated by fluorescence-activated cell sorting, although the CD8+ T cells produced less cytokine and were at a relatively lower frequency. Addition of recombinant IL-10 to the virus-stimulated cultures decreased the amount of IFN-gamma that could be detected, while incorporation of a monoclonal antibody to IL-10 had the opposite effect. A neutralization experiment also indicated that IL-2 was the principal mediator of lymphocyte proliferation. These experiments thus show that the developing T-cell response in the regional lymph nodes of mice with influenza cannot be rigidly categorized on the basis of a TH1 or TH2 phenotype and suggest possible regulatory mechanisms.